2020
DOI: 10.20527/jcae.v3i3.425
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Kemampuan Berpikir Kritis Dan Efikasi Diri Siswa Sma Negeri Kelas Xi Ipa Se Kota Banjarmasin Pada Materi Laju Reaksi

Abstract: Penelitian ini bertujuan mengetahui tingkat kemampuan berpikir kritis siswa SMA Negeri. Populasi dalam penelitian ini adalah seluruh siswa kelas XI SMA Negeri di kota Banjarmasin. Pengambilan sampel dilakukan dengan teknik purposive random sampling artinya dari seluruh populasi dipilih 4 SMA Negeri yang tergolong tinggi yaitu SMA Negeri 2 Banjarmasin, tergolong sedang yaitu SMA Negeri  6 Banjarmasin dan SMA Negeri 8 Banjarmasin dan tergolong rendah yaitu SMA Negeri 12 Banjarmasin. Teknik pengumpulan data mengg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Based on previous research, that the majority of students' self-efficacy levels were in a good category, namely with a percentage of achievement of 66.64%, which means that the level of student confidence in their abilities was equal to that percentage (Nuraeni et al, 2019). A study on SMA XI students in Banjarmasin and found that the self-efficacy of SMAN 2 students was better than students of SMAN 6, SMAN 8, SMAN 12 because they got the highest result, namely 75.5% (Naparin et al, 2020). Curiosity is a powerful motivating force manifested by its capacity to energize and control direction learning behavior such as information seeking and problem-solving (Litman & Jimerson, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Based on previous research, that the majority of students' self-efficacy levels were in a good category, namely with a percentage of achievement of 66.64%, which means that the level of student confidence in their abilities was equal to that percentage (Nuraeni et al, 2019). A study on SMA XI students in Banjarmasin and found that the self-efficacy of SMAN 2 students was better than students of SMAN 6, SMAN 8, SMAN 12 because they got the highest result, namely 75.5% (Naparin et al, 2020). Curiosity is a powerful motivating force manifested by its capacity to energize and control direction learning behavior such as information seeking and problem-solving (Litman & Jimerson, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Self-efficacy is a person's evaluation of his ability or competence to perform a task, achieve goals, and overcome various obstacles (Naparin et al, 2020). Self-efficacy (self-ability) is a very important aspect in today's education world, where a student is required to have the competence that is in him in doing something, one of which is essential in learning today is the ability of a student to speak or speak.…”
Section:  Introductionmentioning
confidence: 99%